The reality of banking financing of the private sector in Oum El bouagui city – the determinants and difficulties- - TOURCHE, ZINAB (Milev Journal of Research and Studies, 2016)
The private sector plays an important role in economic development and contributes to economic growth and job creation, but for doing it, it depends on ability to secure the financing needed to support its creation and development. In this context, public banks are regarded as the main artery that supplies businesses in this sector with the necessary funds. So through this study we tried to analyze the reality of the financing of public banks for the private sector in the wilaya of Oum El Bouagui and to identify the most important problems and difficulties encountered by investors in this sector to obtain the necessary funding.